Optimization of SMES and TCSC using particle swarm optimization for oscillation mitigation in a multi machines power system - Dwi Lastomo; Herlambang Setiadi; Muhammad Ruswandi Djalal (National Research and Innovation Agency, 2017)
Due to the uncertainty of load demand, the stability of power system becomes more insecure. Small signal stability or low-frequency oscillation is one of stability issues which correspond to power transmission between interconnected power systems. To enhance the small signal stability, an additional controller such as energy storage and flexible AC transmission system (FACTS) devices become inevitable. This paper investigates the application of superconducting magnetic energy storage (SMES) and thyristor controlled series compensator (TCSC) to mitigate oscillation in a power system. To get the best parameter values of SMES and TCSC, particle swarm optimization (PSO) is used. The performance of the power system equipped with SMES and TCSC was analyzed through time domain simulations. Three machines (whose power ratings are 71.641, 163, and 85 MW) nine buses power system was used for simulation. From the simulation results, it is concluded that SMES and TCSC can mitigate oscillatory condition on the power system especially in lowering the maximum overshoot up to 0.005 pu in this case. It was also approved that PSO can be used to obtain the optimal parameter of SMES and TCSC.